Outgroup image of host and Latino immigrant adolescents: Influence of intergroup contact and age - Calderón-López, Sonsoles; Navas, Marisol (Anales de Psicología / Annals of Psychology, 2015)
Two studies are presented with the purpose of analyzing outgroup perception of 471 native and 333 Latino immigrant adolescents in Madrid city and differences regarding age and level of outgroup contact. In order to evaluate outgroup perception, a measure was created using descriptions provided by adolescents with similar characteristics during focus groups conducted in a preliminary study. The final measure shows similar structure and appropriate psychometric properties for both participant groups and it evaluates total outgroup perception and its positive and negative components. In line with previous research, Latino adolescents show a more positive outgroup image than the Spaniards; they also express higher scores in both positive and negative outgroup perception. Those adolescents with higher level of outgroup contact show higher scores in total and positive outgroup image, but effects on negative outgroup image differ with group status. Results in relation to age are not concluding. This study contributes to a better understanding of intergroup perception during adolescence, a developmental period in which this research is still limited in Spain.